To speak or not to speak : because they tell me to speak Sámi at daycare - Braut, Kristine Tjåland (Universitetet i Tromsø, 2010)
This thesis is a research of Indigenous language revitalization through preschool children in a language nest. When families cannot themselves provide the language, as are mostly the case in Tysfjord, this language nest strengthens and activates the language. I question to what degree preschool children can contribute to strengthening of an endangered language through acquiring it as a second language outside the home. Children gain good competence to understand and use the language, but it’s still important to take the language more into use, not only between children and employees, but to bring the language home and get it more into free play. The children do observe factors as that the parents and employees communicate together and choose another language. There should ideally be more focus on language-interactions between employees and parents. The status quo is indicative of institutionalizing the language. Parent support is needed to prevent a” daycare language” that is spoken “because they tell me to”. This is a challenge since the parents’ generation themselves has not learned the language or has a stigmatized attitude against speaking it. The language nest is a good foundation to possibility hear and practically use the language daily, but I question if the language nest is a strength when I heard the expression; I don`t speak because it’s the weekend”